Assistance in improving the welfare of foster grandmothers at the Tikung Health Center, Lamongan Regency - Lieliek Soetjiatie; Juliana Christyaningsih; Nur Hatijah (Universitas Muhammadiyah Magelang, 2022)
This community service intends to assist Tikung Health Center foster grandmothers in becoming great grandmothers with healthy toddlers. Because the toddler's mother was at work, the foster grandmother program began with the Posyandu Toddler activity, which was attended by grandmothers taking their grandchildren. As a result, support is still required to improve grandmothers' and grandchildren's nutrition and health awareness. Nutrition education for the elderly, parenting and nutrition education for toddlers, nutrition counseling services and blood glucose checks, and community empowerment through cassava processing competitions (local foods) are all part of this program. The program went off without a hitch, thanks to the foster grandmothers' joyful reception and a lot of help from cadres, PKK, village officials, and the Tikung Health Center in Lamongan Regency. Foster grandmothers' knowledge of parenting and nutrition is also increased, as is their ability to process many varieties of processed cassava, which can provide income opportunities for foster grandmothers and their family.